Step-by-step explanation:
x= -2,
(x - 5) / 2= -6
( (-2) - 5) / 2= -6
(-7) / 2 = -6
-3.5 = - 6
right hand side not equal to left hand side of this equation.so,x= -2 cannot exist for this equation.
x=2,
(x - 5) / 2= -6
(2 - 5) / 2= -6
(-3) / 2= -6
-1.5 = - 6
right hand side not equal to left hand side of this equation.so,x= 2 cannot exist for this equation.
x= -17
(x - 5) / 2= -6
( ( -17) - 5) / 2= -6
(- 22) / 2= -6
-11 = -6
right hand side not equal to left hand side of this equation.so,x= -17 cannot exist for this equation.
x= -7,
(x - 5) / 2= -6
( ( -7) -5) / 2= -6
(-12) / 2= -6
-6= -6
right hand side equal to left hand side of this equation.so,x= -7 exist for this equation.
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️



Add sides 5


Subtract sides 2x


Divide sides by 4


_________________________________
CHECK :



Thus the solution is correct....
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️
Answer:
b x h / 2
Step-by-step explanation:
There is a multiple zero at 0 (which means that it touches there), and there are single zeros at -2 and 2 (which means that they cross). There is also 2 imaginary zeros at i and -i.
You can find this by factoring. Start by pulling out the greatest common factor, which in this case is -x^2.
-x^6 + 3x^4 + 4x^2
-x^2(x^4 - 3x^2 - 4)
Now we can factor the inside of the parenthesis. You do this by finding factors of the last number that add up to the middle number.
-x^2(x^4 - 3x^2 - 4)
-x^2(x^2 - 4)(x^2 + 1)
Now we can use the factors of two perfect squares rule to factor the middle parenthesis.
-x^2(x^2 - 4)(x^2 + 1)
-x^2(x - 2)(x + 2)(x^2 + 1)
We would also want to split the term in the front.
-x^2(x - 2)(x + 2)(x^2 + 1)
(x)(-x)(x - 2)(x + 2)(x^2 + 1)
Now we would set each portion equal to 0 and solve.
First root
x = 0 ---> no work needed
Second root
-x = 0 ---> divide by -1
x = 0
Third root
x - 2 = 0
x = 2
Forth root
x + 2 = 0
x = -2
Fifth and Sixth roots
x^2 + 1 = 0
x^2 = -1
x = +/- 
x = +/- i
Answer:

Step by step explanation:

